2015
DOI: 10.2139/ssrn.2633951
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Student Loan Debt on Small Business Formation

Abstract: Small businesses are the backbone of the U.S. economy and account for approximately one-half of the private-sector economy and 99% of all businesses. To start a small business, individuals need access to capital. Given the importance of an entrepreneur's personal debt capacity in financing a startup business, student loan debt, which is difficult to discharge via bankruptcy, can have lasting effects and may have an impact on the ability of future small business owners to raise capital. This study examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Respondents also shared some impact of their financial circumstances, indicating that they felt stressed out, were anxious about not having enough money, living paycheck-to-paycheck, or having to reconsider their future educational and career plans based on financial limitations. These findings are consistent with broader work demonstrating that individuals with student debt in general are less likely to pursue personal goals, such as buying a home or getting married and starting a family (Ambrose et al, 2015; Puzzanghera, 2015; We Are Hope, 2015). It is disappointing that the pursuit of higher education results in so much economic and personal cost and represents a hardship for many.…”
Section: Discussionsupporting
confidence: 86%
“…Respondents also shared some impact of their financial circumstances, indicating that they felt stressed out, were anxious about not having enough money, living paycheck-to-paycheck, or having to reconsider their future educational and career plans based on financial limitations. These findings are consistent with broader work demonstrating that individuals with student debt in general are less likely to pursue personal goals, such as buying a home or getting married and starting a family (Ambrose et al, 2015; Puzzanghera, 2015; We Are Hope, 2015). It is disappointing that the pursuit of higher education results in so much economic and personal cost and represents a hardship for many.…”
Section: Discussionsupporting
confidence: 86%
“…Large amounts of debt result in less discretionary spending, limited access to other lines of credit (such as a mortgage or automobile loan), and increased risk for defaulting on student loans. Individuals with student loan debt are also less likely get married and start families, purchase homes, or start their own businesses (Ambrose, Cordell, & Ma, 2015; Puzzanghera, 2015; We Are Hope, 2015). Taken as a whole, current trends in cost and debt loads point to a higher education system that is unsustainable.…”
Section: Discussionmentioning
confidence: 99%
“…Student loan debt has become ubiquitous with attending college, so much so that the issue has been labeled a crisis. Research indicated that student loan debt had serious economic effects that included lower home ownership (Ingraham, 2019), restricted small business growth (Ambrose et al, 2015), decreased net worth (Elliot & Nam, 2013), and decreased retirement savings (Rutledge et al, 2018) among debt holders.…”
Section: An Analysis Of the Financial Burden For Students Attending S...mentioning
confidence: 99%